Blastic plasmacytoid dendritic cell neoplasm: a case report from a hospital in Espírito Santo, Brazil (Brazilian Journal of Health Research, 2025)
Introduction: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematologic malignancy with a poor prognosis, slight male predominance, and cutaneous and systemic manifestations. Objective: To describe the clinical, diagnostic, and therapeutic course of a patient with blastic plasmacytoid dendritic cell neoplasm and to discuss the challenges associated with disease recognition and management in light of the literature. Methods: This descriptive, retrospective clinical case report was based on the analysis of clinical, laboratory, imaging, histopathological, and therapeutic data recorded in the patient’s medical records. The case was discussed in the context of a narrative review of the literature. Case report: A 52-year-old woman presented with weight loss, fever, and skin lesions and subsequently developed anemia, leukocytosis, thrombocytopenia, splenomegaly, lymphadenopathy, cutaneous involvement, and refractoriness to chemotherapy. The diagnosis was confirmed by immunohistochemical analysis of an axillary lymph node. The patient received different lines of treatment without a significant response and was subsequently referred to palliative care. Conclusion: BPDCN poses major diagnostic and therapeutic challenges. This report illustrates the clinical course and treatment difficulties associated with a still poorly recognized entity and emphasizes the importance of early clinical suspicion and referral for specialized investigation.
Keywords: Hematologic neoplasms; Dendritic cells; Rare diseases; Differential diagnosis; Palliative care